Guidelines for the management and treatment of periodic fever syndromes familial Mediterranean fever - Terreri, Maria Teresa R.A.; Bernardo, Wanderley Marques; Len, Claudio Arnaldo; da Silva, Clovis Artur Almeida; de Magalhães, Cristina Medeiros Ribeiro; Sacchetti, Silvana B.; Ferriani, Virgínia Paes Leme; Piotto, Daniela Gerent Petry; Cavalcanti, André de Souza; de Moraes, Ana Júlia Pantoja; Sztajnbok, Flavio Roberto; de Oliveira, Sheila Knupp Feitosa; et al. (Elsevier, 2016)
Objective: To establish guidelines based on scientific evidence for the management of familial Mediterranean fever. Description of the evidence collection method: The Guideline was prepared from 5 clinical questions that were structured through PICO (Patient, Intervention or indicator, Comparisonand Outcome), to search key primary scientific information databases. After defining thepotential studies to support the recommendations, these were graduated considering theirstrength of evidence and grade of recommendation. Results: 10,341 articles were retrieved and evaluated by title and abstract; from these,46 articles were selected to support the recommendations. Recommendations: 1. The diagnosis of FMF is based on clinical manifestations, characterized by recurrent febrile episodes associated with abdominal pain, chest or arthritis of large joints. 2. FMF is a genetic disease presenting an autosomal recessive trait, caused by mutation in the MEFV gene. 3. Laboratory tests are not specific, demonstrating high serum levels of inflammatory proteins in the acute phase of the disease, but also often showing high levels even between attacks. SAA serum levels may be especially useful in monitoring the effectiveness of treatment. 4. The therapy of choice is colchicine; this drug has proven its effectiveness in preventing acute inflammatory episodes and progression toward amyloidosis in adults. 5. Based on the available information, the use of biological drugs appears to be an alternative for patients with FMF who do not respond or are intolerant to therapy with colchicine.
Keywords: Autoinflammatory syndromes; Childhood; Familial Mediterranean fever; Fever; Guidelines